Generalized structured component analysis (GSCA) method in evaluating service satisfaction at FMIPA Syiah Kuala University - EVI RAMADHANI; NURJARIATI NURJARIATI; NURHASANAH NURHASANAH; NANY SALWA; LATIFAH RAHAYU SIREGAR (Universitas Syiah Kuala, 2023)
This research focuses on the Generalized Structured Component Analysis (GSCA) method in evaluating service satisfaction at FMIPA Syiah Kuala University (USK). FMIPA USK is expected to have good service quality to satisfy stakeholders with the services provided. FMIPA USK needs to know the factors that affect service satisfaction. An internal survey of the integrity zone is one way to determine the quality and satisfaction of the services provided by FMIPA USK. However, this survey uses indirect variables, so the structural equation model (SEM) can be used. The SEM method used in this study is component-based SEM, namely Generalized Structured Component Analysis (GSCA). GSCA is used because questionnaires do not fulfill existing assumptions in general research, and the GSCA method does not require many assumptions. This research aims to form a model, determine the relationship between indicators and latent variables, and know the relationship between latent variables and the factors significantly affecting student satisfaction with services at FMIPA USK. The results of this study show that the indicators used are valid and reliable. Reliability, assurance, empathy, and tangibles is a factor that affects service satisfaction. Models formed in this study have a GFI value of 0.962 and SRMR of 0.365, so the model used is suitable.